METROLOGY IN THE QUALITY SYSTEM AT RUP “BMZ” - E. V. Borisenko (Литьë и металлургия)
The main aim at creating of quality system, which was set by metrologists of RUP “BM Z”, is providing of high quality of testing and calibration.